2010
DOI: 10.1021/jp1013237
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Genomic DNA: A Photoemission and X-ray Absorption Study

Abstract: The electronic structure of genomic DNA has been comprehensively characterized by synchrotron-based X-ray absorption and X-ray photoelectron spectroscopy. Both unoccupied and occupied states close to the Fermi level have been unveiled and attributed to particular sites within the DNA structure. A semiconductor-like electronic structure with a band gap of approximately 2.6 eV has been found at which the pi and pi* orbitals of the nucleobase stack make major contributions to the highest occupied and lowest unocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 73 publications
4
30
0
Order By: Relevance
“…The electronic structure of DNA has been investigated both experimentally [8][9][10][11][12][13] and theoretically [14][15][16][17][18][19][20][21][22][23][24][25] for quite some time. Scanning tunneling spectroscopy and direct measurements of electrical conductivity have been used to explore the electronic structure of DNA but the results obtained were usually not consistent with each other due to differences in the specific experimental setups, the methods of sample preparation, and the ways that the experiments were conducted by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of DNA has been investigated both experimentally [8][9][10][11][12][13] and theoretically [14][15][16][17][18][19][20][21][22][23][24][25] for quite some time. Scanning tunneling spectroscopy and direct measurements of electrical conductivity have been used to explore the electronic structure of DNA but the results obtained were usually not consistent with each other due to differences in the specific experimental setups, the methods of sample preparation, and the ways that the experiments were conducted by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…This dipole-based beamline provides a moderate photon flux distributed continuously over a wide photon energy range from 30 to 1500 eV and, therefore, is particularly suited for radiation sensitive and fragile materials research5556. XPS spectra were acquired with a hemispherical Phoibos 150 electron energy analyzer (Specs GmbH).…”
Section: Methodsmentioning
confidence: 99%
“…Th ere was no resonant peak structure (420 eV). Recently, Kummer et al (2010) reported Observation of DNA cleavage by XANES 891 peak was assigned to the electronic transition from the O 1s orbital to the unoccupied π * (N -C ϭ O) orbital. Figure 4 (a, c, e, g) shows the XANES spectra of each nucleotide (dAMP, TMP, dGMP, and dCMP) fi lm, respectively, around the nitrogen K -edge region following its exposure to 560 eV soft X-rays for 15 min (4 ϫ 10 14 photons), while Figure 4 (b, d, f, h) shows the diff erences between the spectra before and after irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Th ere was no resonant peak structure (550 eV). Kummer et al (2010) assigned the resonant peaks in the XANES spectrum of DNA fi lm. Th e peak at 531.5 eV Figure 4.…”
Section: Methodsmentioning
confidence: 99%